2000
DOI: 10.1034/j.1399-3054.2000.110105.x
|View full text |Cite
|
Sign up to set email alerts
|

ACC oxidase is found in seedlings of two (Coniferales, Gnetales) of the four gymnosperm orders

Abstract: Leaf material and seedlings of species representing all gymnosperm orders were tested for 1‐aminocyclopropane‐1‐carboxylate (ACC) oxidase activity. Seedlings of Pinus nigra, Pinus radiata, Pseudotsuga menziesii, Cupressocyparis leylandii, Ephedra major and E. nevadensis showed high level in vitro ACC oxidase activity. The enzyme from seedlings of Pinus nigra var. nigra (Arnold) was shown to resemble the angiosperm enzyme in a requirement for ascorbate, carbon dioxide and Fe(II). In contrast, seedlings of Ginkg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…ACO from C. chinensis seeds shows the highest activity in Tricine buffer (data not shown). Our work showed that ACO from C. chinensis has a pH optimum close to 7.0, similar to the enzyme obtained from carnation petals (Nijenhuis-de Vries et al 1994), corn and sunflower (Finlayson et al 1997), and ACO from seedlings of Pinus nigra (Reynolds & John 2000). Other reports showed that optimum pH for in vitro activity of ACO isolated from apple fruit was 7.2 and 7.6 depending on the extraction buffers (Kuai & Dilley 1992).…”
Section: Extraction and Incubation Conditionssupporting
confidence: 86%
“…ACO from C. chinensis seeds shows the highest activity in Tricine buffer (data not shown). Our work showed that ACO from C. chinensis has a pH optimum close to 7.0, similar to the enzyme obtained from carnation petals (Nijenhuis-de Vries et al 1994), corn and sunflower (Finlayson et al 1997), and ACO from seedlings of Pinus nigra (Reynolds & John 2000). Other reports showed that optimum pH for in vitro activity of ACO isolated from apple fruit was 7.2 and 7.6 depending on the extraction buffers (Kuai & Dilley 1992).…”
Section: Extraction and Incubation Conditionssupporting
confidence: 86%
“…In addition, exogenous ethylene application can increase resin production and the number of resin ducts in several conifer species (Telewski et al 1983;Yamamoto and Kozlowski 1987;Katoh and Croteau 1997;. ACO activity, the Wnal step in ethylene formation, has previously been detected in several conifer species (Plomion et al 2000;Reynolds and John 2000;Klintborg et al 2002), but little is known about the corresponding ACO genes, their expression and cellular localization in conifers and the relationship of ACO with ethylene production and activities of specialized cells for phenolic or terpenoid formation after wounding in stems.…”
Section: Discussionmentioning
confidence: 97%
“…No ACC oxidase activity was found in needles or buds, although ACC oxidase activity was high in the cambial region (Figure 3). Similarly, Reynolds and John (2000) reported that in vitro ACC oxidase activity was absent from leaf extracts of several conifer species, including Pinus nigra Arnold and Pinus radiata D. Don, whereas seedling extracts of the same species showed high activity. Nevertheless, needles and buds can convert ACC to ethylene, as evidenced by their high rate of ethylene evolution (Figure 4).…”
Section: Monthmentioning
confidence: 88%
“…It is either converted to ethylene by ACC oxidase or conjugated to malonyl-ACC (MACC) by ACC malonyltransferase (Abeles et al 1992, Martin and or to glutamyl-ACC (GACC) by ACC-γ-glutamyltranspeptidase . 1-Amino-cyclopropane-1-carboxylic acid oxidase activity, measured as the ability to convert ACC to ethylene, has been observed in many conifers (Chen et al 1990, Chen and Welburn 1991, Ievinsh and Tillberg 1995, Ingemarsson and Bollmark 1997, Kruzmane and Ievinch 1999, Reynolds and John 2000. There is also evidence that conifers contain conjugated ACC (Yang et al 1993, Christmann and Frenzel 1997, Ingemarsson and Bollmark 1997.…”
Section: Introductionmentioning
confidence: 99%